Toxic dilatation of the colon. (March 2015) - Magee, Cormac; Blackwell, Victoria; Travis, Simon
Abstract Toxic megacolon (TM) is defined as total or non-segmental obstructive dilatation of the colon to an external diameter of 6.0 cm or greater, associated with systemic toxicity. It is a potentially fatal condition that represents the end of a spectrum of severe colitis. Typically a complication of ulcerative colitis, it is also seen as a consequence of infective colitis. Of particular concern, due to its high mortality, is TM associated with pseudomembranous colitis due to Clostridium difficile infection.